2018
DOI: 10.1007/978-3-319-99040-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Industry 4.0 Readiness Indexes and Maturity Models and Proposal of the Dimension for Enterprise Information Systems

Abstract: The article deals with the analysis of available readiness indexes and maturity models for Industry 4.0. The main goal is to determine the extent to which these models and indexes are able to show a company's readiness from the point of view of its information system. Because this topic is not sufficiently dealt with in the available models there is a proposal focusing on the enterprise information system in the conclusion of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…Zvetko et al [54] proposed an Industry 4.0 assessment model for regional development. The above research shows that various maturity models or assessments (see Table 1) have certain validity on the maturity level of smart manufacturing [6,7,52,[54][55][56][57][58][59][60][61][62][63][64].…”
Section: Maturity Assessment Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Zvetko et al [54] proposed an Industry 4.0 assessment model for regional development. The above research shows that various maturity models or assessments (see Table 1) have certain validity on the maturity level of smart manufacturing [6,7,52,[54][55][56][57][58][59][60][61][62][63][64].…”
Section: Maturity Assessment Modelmentioning
confidence: 99%
“…Canetta et al [65] reported that most studies have used standard models for digital maturity assessments, but these models do not illustrate the practical process of transformation. Basl [55] pointed out that using the model to assess maturity can be done at both the macro (social or national) and micro (enterprise) levels. PwC [6] provides an online tool to assess the level of maturity of the enterprise to determine the next step of improvement actions.…”
Section: Maturity Assessment Modelmentioning
confidence: 99%
“…The Fourth Industrial Revolution represents transformation to new systems that bring together physical and digital technologies to an increasingly connected population of active users. Vast academic literature exploring the enabling technologies, benefits, opportunities, enablers, challenges, readiness, maturity and transformation strategies for Industry 4.0 [I4.0] has been published in the last three years (Basl, 2018). These studies emphasize the enhancement from isolated industrial activities to an integrated and automated value chain (Strange and Zucchella, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In such analysis, many variations of improvements come into being and there are too many possible combinations of their implementation. If it is not possible to test all determined arrangements, we only analyse the variants, which are chosen on the basis of our opinion, intuition and our knowledge about the research object [1][2][3].…”
Section: Introductionmentioning
confidence: 99%